2022
DOI: 10.1177/20552076221093133
|View full text |Cite
|
Sign up to set email alerts
|

The bright side of social network sites: On the potential of online social capital for mental health

Abstract: Social network sites are an essential part of the daily lives of people around the globe, but our theoretical understanding of the phenomenon is still limited. However, to fully grasp the potential of social network sites and to be able to generate meaningful applications, a theoretical understanding of the phenomenon is needed. I want to introduce the concept of online social capital as the first step in this direction, and show how it could be applied to the area of mental health. Therefore, I will (1) bring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 54 publications
1
3
0
2
Order By: Relevance
“…Consistent with recent literature (Bae, 2019 ; Hussenoeder, 2022 ), the present study demonstrated how adolescents’ social media use can help build social capital. Accumulating social capital has valuable implications for satisfying competence.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with recent literature (Bae, 2019 ; Hussenoeder, 2022 ), the present study demonstrated how adolescents’ social media use can help build social capital. Accumulating social capital has valuable implications for satisfying competence.…”
Section: Discussionsupporting
confidence: 91%
“…New clinical approaches like telehealth and behavioral intervention technologies allow for services to reach those often underserved or isolated, whether through financial disparities or geographic isolation [ 66 , 67 ]. The relationship between Facebook’s SCI and the indicated relationship to social capital in the United States points toward the potential for new approaches to mental health intervention through social networking sites, through which clinicians and policy makers can target and reach populations in need [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Así, el problema que señalan las participantes está en la falta formación y preparación de las personas que difunden esta información. En este sentido Hussenoeder (2022) propone dar formación y preparación a los denominados creadores de contenido, convirtiéndolos en «influencers de la salud mental», capacitándolos así para dar una información válida y fiable de una manera favorecedora para la prevención. Así mismo, también sería conveniente que las tareas de prevención en las RRSSVV fueran coordinadas o supervisadas por autoridades competentes que aseguren la fiabilidad de dicha información (Latha et al, 2020).…”
Section: Discussionunclassified
“…Así mismo, algunos autores han probado que las RRSSVV pueden servir como un instrumento de concienciación, educación y alfabetización en salud mental, puesto que son herramientas de uso diario y facilitan llegar a más personas a la vez con la inversión de menos recursos (Khaleghi et al, 2019;Latha et al 2020). Así mismo, estas tareas de concienciación y educación también podrían servir para reducir el estigma que rodea los trastornos de salud mental, contextualizándose en un ambiente divertido y agradable que ayudaría a mantener la motivación en torno a estas intervenciones (Hussenoeder, 2022).…”
Section: Rrssvv Como Medios De Información Y Educación Para La Saludunclassified